Anxiety of Not to be Appointed as a Predictor of Pre-service Teachers' Motivation to Teach - Zincirli, Muhammed (BİLGE AKADEMİK YAYINCILIK EĞİTİM BİLİŞİM VE DANIŞMANLIK HİZMETLERİ, 2021)
It is necessary to have a good teacher training policy so that education and training activities can achieve their goals. Well-trained teachers will also lead to an increase in the quality of education. A well-trained teacher is expected to have a high motivation on many issues. The motivation to teach is one of the types of motivation that a teacher should have in the education and training process. Interest and aptitude to teach are among the determining factors of the motivation to teach. There are many variables associated with the motivation to teach. One of them is the anxiety of not to be appointed which can be described as the anxiety about not being employed as a result of the education received. The aim of this study was to determine the effect of pre-service teachers’ anxiety of not to be appointed on their motivation to teach. To this end, this study was conducted in the relational screening model with pre-service teachers studying in the final year of Fırat University Faculty of Education and in the pedagogical formation education program of the same faculty. As a result of the study, it was determined that pre-service teachers’ motivation to teach and anxiety of not to be appointed were high. Another result was that pre-service teachers’ motivation to teach decreased as their anxiety of not to be appointed increased.
Keywords: Other Fields of Education; Alan Eğitimleri